Manajemen Kesiswaan Terhadap Hasil Belajar Siswa - Putri, Mutia (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2021)
The purpose of this study was to describe the effect of student management on student learning outcomes. This student management is specifically related to the form of student guidance in learning. This study applies the literature review method and in collecting research data reviews articles. From the research results, it is known that student management is very influential on student learning outcomes. Because the role of studentmanagement is student management from the beginning of registration, the learning process to graduation. Student management also has an influence on student learning success because the teaching and learning process is more focused which produces students who excel.